Multimodal exercises integrated with cognitive-behavioural therapy improve disability of patients with failed back surgery syndrome: a randomized controlled trial with one-year follow-up - Monticone, Marco; Ambrosini, Emilia; Rocca, Barbara; Cazzaniga, Daniele; Liquori, Valentina; Lovi, Alessio; Brayda-Bruno, Marco (Disability and rehabilitation, 2022)
To evaluate the effect of multimodal exercises integrated with cognitive-behavioural therapy on disability, pain, and quality of life in patients suffering from failed back surgery syndrome (FBSS), and to appraise its extent in the long term. By means of a parallel-group superiority-controlled trial, 150 outpatients were randomly assigned to a 10-week individual-based multimodal programme of task-oriented exercises integrated with cognitive-behavioural therapy (experimental group, 75 patients) or individual-based general physiotherapy (control group, 75 patients). Before treatment, 10 weeks later (post-treatment), and 12 months after the end of treatment, the Oswestry Disability Index (primary outcome), the Tampa Scale for Kinesiophobia, the Pain Catastrophising Scale, a pain intensity numerical rating scale and the Short-Form Health Survey were evaluated. Linear mixed model analysis for repeated measures was carried out for each outcome measure. Significant group ( < 0.001), time ( < 0.001), and time-by-group interaction ( < 0.001) effects were found for all outcome measures. Concerning disability, between-group differences (95% confidential interval) in favour of the experimental group of -9 (-10.7; -7.3) after training and of -13.2 (-14.7; -11.7) at follow-up were found. Also, kinesiophobia, catastrophising and pain showed significant between-group differences of 9, 12.5 and 1.7 points, respectively. The multimodal intervention proposed was superior to general physiotherapy in reducing disability, kinesiophobia, catastrophising, and enhancing the quality of life of patients with FBSS. The effects were reinforced one year after the programme ended.IMPLICATIONS FOR REHABILITATIONMultimodal exercises integrated with cognitive-behavioural therapy induced significant improvements in disability, pain, kinesiophobia, catastrophising, and quality of life of subjects with Failed Back Surgery Syndrome.A well-integrated rehabilitative team which contributes towards reaching intervention goals is advised.Physiotherapists should adopt task-oriented exercises to promote an earlier return to common activities of disabled patients.Psychologists should explain how to modify useless beliefs and support adequate behaviours, in order to produce constructive attitudes towards perceived disability.